MONITORING DAN EVALUASI (MONEV) PEMBELAJARAN DARING SEMESTER GENAP TAHUN AJARAN 2020/2021 DI UNIVERSITAS QUALITY BERASTAGI - Ferdinand Sinuhaji (Universitas Quality, 2022)
The purpose of this study is to determine the extent of the implementation of online learning at Berastagi Quality University, to identify problems that arise during the implementation of online learning, to describe solutions and recommendations for problems related to the implementation of online learning, where and when to implement activities. This research is a descriptive research by conducting a survey using google form. The population used were students of Quality Berastagi University while the sample was selected using purposive sampling technique with the sample being students of Quality Berastagi University. The number of student samples is 212 people. The instrument used is a Likert scale. Data collection techniques were carried out by distributing online questionnaires to Quality Berastagi University students with the aim of obtaining relevant and valid information. The research procedure taken was compiling statements for the questionnaire, validating and reliable questionnaires, collecting data by distributing validated questionnaires online to lecturers and students and conducting descriptive analysis. The results of the online learning monitoring and evaluation for the even semester of the 2020/2021 academic year at the University of Quality Berastagi is that in online learning planning 47.6% of students gave good results, 26.9% was quite good and 18.4% was very good. The results of online learning for the total performance results are 44.725% in the Good category, 17.5% very good, 26.5% quite good. The results of online learning interactions with total performance results are 47.66% good category, 21.54% very good and 23.3% quite good. The results of the evaluation of the implementation of online learning that have been carried out can be well received by students 50.5% good, 17% very good and 23.3% quite good.